Enhancing EMR Programming through a TPACK-Based Interactive Application in Health Informatics Education - widiyanto, Wahyu Wijaya; Nugroho, Suryanto; Widyaningrum, Bajeng Nurul (Jurnal Inotera, 2025)
This study explores the potential of an interactive learning application, designed using the Technological Pedagogical Content Knowledge (TPACK) and Self-Regulated Learning (SRL) frameworks, to enhance student competence in basic Electronic Medical Record (EMR) programming within health informatics education. Using a quasi-experimental pretest-posttest design, the research involved 64 third-semester students in a vocational Health Information Management program. Participants were divided into two groups: an experimental group utilizing the interactive application and a control group receiving traditional instruction. Data were collected through achievement tests, motivation surveys, and usage log analysis. Results revealed that the experimental group demonstrated significantly higher learning achievement (M = 78.6 vs. 65.9), improved motivation (Likert mean = 4.35), and stronger self-regulated learning behaviors (87.1% module completion and 81% repeated simulations). These findings suggest that interactive tools grounded in pedagogical frameworks can effectively bridge abstract programming logic with clinical relevance, fostering both engagement and autonomous learning. The study contributes a scalable and replicable model for integrating simulation-based programming instruction in health informatics curricula.